If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(7*x)/3 = 11
3;4;0;0;4;0
(5*x)/4-(1/5) = 1-((2/5)*(x-(1/10)))
(5*x)/2-9 = (2*x-7)/6
x-0.75 = 2/4
| a=h^2-4 | | 4x-2=8x-13 | | 6x-2-8x+3=40x+8 | | -148=3(7x-8)+2 | | 7x/3=11 | | log(2x-1)-log(x-1)=x | | (5x-3)-(2x+1)= | | 450x-8000=720x-13000 | | -9(3m-9n+5p)= | | 2.5x-10=h | | 5m+7m-13=15m | | 2x+3x-7x= | | (a+b^2)=a^2+2ab+b^2 | | -8-2(3-9)=0 | | (-3x+2)+(5x-1)= | | ((5x)/4)-(1/5)=1-(2/5)(x-(1/10)) | | -113=-7(-2x+3) | | (X^2-5x+4)(x^2+7x-3)= | | 15x+10+5x=8 | | (5-3x)+(2x+4)= | | .75x-.2x+.8=5x | | 2x+3-4= | | 4x^2-21xy-25y^2=0 | | 36=.44*w | | 3x+5x+15=10 | | X(5x-2)+x(2x-3)=(7x+8)(x-3) | | (3+4x)+(x-2)= | | 36=.43*w | | 100(15t+4.75)=143.25 | | fx=4cos(2x) | | B=12.89+-8s | | ((5x)/2)-9=(2x-7)/6 |